Interaction of deformation-strength characteristics of the support load-bearing elements in the preparatory workings - Kovalevska Iryna; Barabash Mykhailo; Husiev Oleksandr; Snihur Vasyl (E3S Web of Conferences, 2018)
The objective of this work is to study the relationship of the deformation-strength characteristics of the fastening system with its displacement value. The tendencies of influence are divided into two groups. The multivariate computational experiments have been performed in the conditions of coal-face works. It is shown the influence of geomechanical conditions of the mine working maintenance on the fastening system operating mode change when choosing its rational deformation-strength characteristics. On the basis of the performed studies, it was concluded that it is necessary to adjust the fastening elements of each specific support setting scheme. This is necessary to provide recommendations for the maintenance schemes optimization of reusable extraction workings.